Copper(I)-catalyzed acid-controlled divergent radical cyclization of 1,6-enynes to access 1-indanones and 1H-cyclopropa[b] naphthalene-2,7-diones - Jamshidi, Elmira; Rajai-Daryasarei, Saideh; Stranger, Robert; Ariafard, Alireza; Rominger, Frank; Balalaie, Saeed (Chemistry - a European journal, 2025)
Abstract 1-Indanone derivatives are efficiently synthesized via a radical cyclization reaction of 1,6-enynes, using TBHP as both oxidant and reactant, in the presence of Cu(I) as the catalyst and 4-methyl benzoic acid as the cocatalyst. Notably, in the absence of 4-methyl benzoic acid, the reaction undergoes a dramatic shift in product selectivity, yielding 1H?cyclopropa[b]naphthalene-2,7-diones exclusively under the same conditions, with Cu(I) acting as the sole catalyst. This transformation offers key advantages, including operational simplicity, cost-effective and readily available materials, scalability to gram quantities, and compatibility with a wide range of functional groups. Mechanistic studies and DFT calculations confirmed that the reaction proceeds through a radical pathway, highlighting the pivotal role of 4-methylbenzoic acid as the cocatalyst in altering product selectivity.
Zuerst veröffentlicht: 07. April 2025
Gesehen am 15.09.2025